Un écoféminisme à la française ? Les liens entre mouvements féministe et écologiste dans les années 1970 en France - Isabelle Cambourakis (Genre & Histoire)
This article reconsiders the period following the events of May 1968 in France, the re-emergence of the ecologist and feminist movements and the attempt to bring them together through a systematic analysis of ecologist (La Gueule ouverte and Le Sauvage) and feminist (Sorcières, des femmes en mouvement, etc.) magazines, together with interviews carried out with journalists and activists. It analyses in particular three aspects of efforts to make these movements converge: the attempts to organize meetings and coalitions between the ecologist movement and some feminists; the theoretical links proposed by Françoise d’Eaubonne from 1974 surrounding the concept of eco-feminism; and the growing interest in ecology of some differentialist feminists situated at the junction of various social movements. This article highlights the specificity of the French situation at the end of the 1970s as a transnational ecofeminist movement emerged.